The association between dietary branched-chain amino acids and the risk of cardiovascular diseases in Chinese patients with type 2 diabetes: A hospital-based case–control study - Zheng, Lu; Cai, Jun; Feng, Yong-hui; Su, Xin; Chen, Shi-yun; Liu, Jia-zi; Li, Wan-lin; Ouyang, Rui-qing; Ma, Jun-rong; Cheng, Chen; Mu, Ying-jun; Zhang, Shi-wen; et al. (Frontiers in Nutrition, 2022)
Background: Previous studies showed conflicting evidences on the association between intake of dietary branched-chain amino acids (BCAA) and the risk of cardiovascular disease (CVD). However, this relationship has not been studied in type 2 diabetes patients. Therefore, we evaluated the effects of total and individual dietary BCAA (leucine, isoleucine and valine) intake on CVD risk among type 2 diabetes individuals in China. Materials and methods: A total of 419 patients with type 2 diabetes who have diagnosed with CVD (within 2 weeks) were recruited between March 2013 and September 2015 in China. Cases with CVD were 1:1 matched to controls with type 2 diabetes but without CVD by age (± 5 years) and sex. A validated 79-item semiquantitative food frequency questionnaire (FFQ) was administered to assess the participants’ dietary data. Total dietary BCAA per individual was the summation of daily intake of isoleucine, leucine and valine. OR and corresponding CIs were computed by conditional logistic regression models adjusted for potential confounders. Results: Median values of daily intake of total BCAA were 11.87 g, with an interquartile range of 10.46-13.15 g for cases and 12.47 g, with an interquartile range of 11.08-13.79 g for controls (P value = 0.001). Dietary BCAA was inversely related to CVD risk after multivariable adjustment (OR Q4-Q1 = 0.23, 95%CI = 0.10, 0.51, P trend <0.001 for total BCAA; OR Q4-Q1 = 0.20, 95%CI = 0.07, 0.53, P trend = 0.001 for leucine). For each 1-S.D. increase of total dietary BCAA, leucine or valine intake was associated with 54% (95%CI = 29%, 70%, P value = 0.001), 64% (95%CI =29%, 82%, P value = 0.003), or 54% (95%CI = 1%, 79%, P value = 0.049) decreased in the risk of CVD, respectively. Whole grains, starchy vegetables, mushrooms, fruit, eggs and dairy and dairy products derived BCAA were found to attenuate CVD risk (P value ranged: = 0.002-0.027). Conclusions: Higher BCAA intake, in particular leucine and valine, might be associated with a lower risk of CVD.